importance of wood traits and hydraulic conductance for the performance and life history strategies of 42 rainforest tree species - Poorter, Lourens; McDonald, Imole; Alarcón, Alfredo; Fichtler, Esther; Licona, Juan-Carlos; Peña-Claros, Marielos; Sterck, Frank; Villegas, Zulma; Sass-Klaassen, Ute (The New phytologist, 2010)
In a comparative study of 42 rainforest tree species we examined relationships amongst wood traits, diameter growth and survival of large trees in the field, and shade tolerance and adult stature of the species. The species show two orthogonal axes of trait variation: a primary axis related to the vessel size-number trade-off (reflecting investment in hydraulic conductance vs hydraulic safety) and a secondary axis related to investment in parenchyma vs fibres (storage vs strength). Across species, growth rate was positively related to vessel diameter and potential specific hydraulic conductance (Kp), and negatively related to wood density. Survival rate was only positively related to wood density. Light-demanding species were characterized by low wood and vessel density and wide vessels. Tall species were characterized by wide vessels with low density and large Kp. Hydraulic traits were more closely associated with adult stature than with light demand, possibly because tall canopy species experience more drought stress and face a higher cavitation risk. Vessel traits affect growth and wood density affects growth and survival of large trees in the field. Vessel traits and wood density are therefore important components of the performance and life history strategies of tropical tree species.